Lekcja jako dyskurs - Kudra, Andrzej (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2001)
The author treats the lesson as a discussion, a communicative event. Therefore, the lesson becomes a process, not just an effect with a dialogue structure. The author preceeds further – the lesson with verbal, vocal and non-verbal communicative activities, genders of speech and methods is seen as a text.